SUPPORT GROUP DAN PSYCHOLOGICAL WELL BEING IBU DARI ANAK TULI DITINJAU DARI STRATEGI COPING - Rizka Azaria Usa Lizhardy; IGAA Novi Ekayati; Dyan Evita Santi (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
This study aims to determine the effectiveness of support groups on psychological well-being of mothers of deaf children in terms of coping strategies. This study used a pre-experimental design method (quasi-experimental). The experimental design type is the one group pretest-postest type. This type of design used only one experimental group and took measurements before and after the treatment of the subjects. This study was conducted on mothers of deaf children who had low and moderate psychological well-being with a total sample of 30 people using the purposive sampling method. The results showed that the first hypothesis using independent sample t-test analysis was accepted, meaning that the support group was effective in improving psychological well-being in mothers of deaf children. The results of the second hypothesis test using independent sample T-test analysis were accepted, meaning that there was no difference in psychological well-being improvement among mothers of Deaf children who used problem focused coping and emotion focused coping.